Rotation and internal structure of Population III protostars - Stacy, Athena; Greif, Thomas H.; Klessen, Ralf S.; Bromm, Volker; Loeb, Abraham (Monthly notices of the Royal Astronomical Society, 2013)
We analyse the cosmological simulations performed in the recent work of Greif et al., which followed the early growth and merger history of Population III (Pop III) stars while resolving scales as small as 0.05 R⊙. This is the first set of cosmological simulations to self-consistently resolve the rotation and internal structure of Pop III protostars. We find that Pop III stars form under significant rotational support which is maintained for the duration of the simulations. The protostellar surfaces spin from ∼50 per cent to nearly 100 per cent of Keplerian rotational velocity.These rotation rates persist after experiencing multiple stellar merger events. In the brief time period simulated (∼10 yr), the protostars show little indication of convective instability, and their properties furthermore show little correlation with the properties of their host minihaloes. If Pop III protostars within this range of environments generally form with high degrees of rotational support, and if this rotational support is maintained for a sufficient amount of time, this has a number of crucial implications for Pop III evolution and nucleosynthesis, as well as the possibility for Pop III pair-instability supernovae, and the question of whether the first stars produced gamma-ray bursts.
Gesehen am 15.02.2022